Underway physical oceanography during GOAL cruise ESTARTE (2014) - Rodrigo Kerr; Iole Beatriz Marques Orselli (PANGAEA, 2025)
This dataset contains sea surface temperature, sea surface salinity, dissolved oxygen, and partial pressure of carbon dioxide measured underway in the shelf-break region of the South Brazil Bight (SBB) and Southern Brazilian Shelf (SBS) between 23 to 33 of south latitude in October 2014. These measurements were made during the EstARte cruise carried out by the Brazilian Ocean Acidification Network (BrOA) and High Latitude Oceanography Group (GOAL_FURG). The EstARte project aims to obtain physical and biogeochemical processes controlling carbon exchanges at the air-sea interface and ocean acidification in the South Atlantic continental shelf and slope. Salinity, temperature, and dissolved oxygen were measured using a multiparameter sensor, and the carbon dioxide measurements were obtained using an autonomous system equipped with a non-dispersive infrared gas analyzer.